Global chlorophyll responses to marine heatwaves in satellite ocean color - Kyung Min Noh; Hyung-Gyu Lim; Jong-Seong Kug (Environmental Research Letters, 2022)
Marine heatwaves (MHWs), prolonged ocean temperature extremes, have been enhanced by global warming in recent decades. More intense and longer MHWs have increasingly negative impacts on marine organisms that threaten their resilience of marine ecosystems. In this study, we investigated global marine phytoplankton biomass (chlorophyll) estimated by satellite ocean color and its response to MHWs on global and regional scales. We find that MHWs typically decreases chlorophyll concentrations in the tropics and mid-latitudes, with increases at high latitudes. The magnitude of chlorophyll responses to MHWs is increased in response to higher intensity and longer duration of MHWs. We find a change in the response from negative to positive chlorophyll responses to MHWs across the 40°–50° latitude bands in both hemispheres where the strongest meridional gradient in nitrate concentration exists. In these response-changing regions, the latitudinal contrast of the chlorophyll response is more distinctive in the warm season rather than in the cold season because of the shallower climatological mixed layer. The present study highlights the global phytoplankton responses to MHWs and their sensitivity to MHWs properties that imply the importance of upper-ocean interactions between phytoplankton and the mixed-layer.